How wise companies drive digital transformation - Giovanni Schiuma; Eva Schettini; Francesco Santarsiero (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Enterprises aimed at acquiring a sustainable competitive advantage in the Digital Era are challenged to develop a Transformative Digital Leadership marked by a set of abilities. The paper introduces the Digital Transformative Leadership Compass as an innovative framework to assess wise leaders' characteristics driving organisational digital transformation in today's complex business landscape. It identifies the critical abilities, attitudes, and behaviours distinguishing the profile of a transformative digital leader leading an organisation to continuously innovate and digitally evolve in the same way as the business landscape. This paper contributes to theory building by proposing an interpretative framework of critical abilities distinguishing a transformative digital leader of a transformative digital company. Furthermore, the paper provides practitioners with valuable insights and theoretical evidence on leadership practices in the digital era.
Keywords: 650; abilities; digital transformation; leadership; soft skills; transformative enterprises; wise leader